Auxin Response Factor 2A Is Part of the Regulatory Network Mediating Fruit Ripening Through Auxin-Ethylene Crosstalk in Durian - Khaksar, Gholamreza; Sirikantaramas, Supaart (Frontiers in Plant Science, 2020)
Fruit ripening is a highly coordinated developmental process driven by a complex hormonal network. Ethylene is the main regulator of climacteric fruit ripening. However, a putative role of other key phytohormones in this process cannot be excluded. We previously observed an increasing level of auxin during the post-harvest ripening of the durian fruit, which occurred concomitantly with the rise in the climacteric ethylene biosynthesis. Herein, we connect the key auxin signaling component, auxin response factors (ARFs), with the regulatory network that controls fruit ripening in durian through the identification and functional characterization of a candidate ripening-associated ARF. Our transcriptome-wide analysis identified 15 ARF members in durian (DzARFs), out of which 12 were expressed in the fruit pulp. Most of these DzARFs showed a differential expression, but DzARF2A had a marked ripening-associated expression pattern during post-harvest ripening in Monthong, a commercial durian cultivar from Thailand. Phylogenetic analysis of DzARF2A based on its tomato orthologue predicted a role in ripening through the regulation of ethylene biosynthesis. Transient expression of DzARF2A in Nicotiana benthamiana leaves significantly upregulated the expression levels of ethylene biosynthetic genes, pointing to a ripening-associated role of DzARF2A through the transcriptional regulation of ethylene biosynthesis. We previously reported significantly higher auxin level during post-harvest ripening in a fast-ripening cultivar (Chanee) compared to a slow-ripening one (Monthong). DzARF2A expression was significantly higher during post-harvest ripening in the fast-ripening cultivars (Chanee and Phuangmanee) compared to that of the slow-ripening ones (Monthong and Kanyao). Thus, higher auxin level could upregulate the expression of DzARF2A during ripening of a fast-ripening cultivar. The auxin-induced expression of DzARF2A confirmed its responsiveness to exogenous auxin treatment in a dose-dependent manner, suggesting an auxin-mediated role of DzARF2A in fruit ripening. We suggest that high DzARF2A expression would activate ARF2A-mediated transcription of ethylene biosynthetic genes, leading to increased climacteric ethylene biosynthesis (auxin-ethylene crosstalk) and faster ripening. Hence, we define DzARF2A as a new component of the regulatory network mediating durian fruit ripening through an intense interplay between auxin and ethylene.